Airframe Vibration Control Simulation Of A Medium Utility Helicopter Using A Higher Harmonic Control System - Kim, D.H.; Park, J.S.; Kim, D.G.; Kang, W.R. (My University, 2024)
A numerical simulation of the airframe vibration control of a medium utility helicopter using the higher harmonic control (HHC) system has been performed. The HHC system operates independently of the primary control system. For the aeromechanical analysis, CAMRAD II is used to model the target aircraft including the main rotor, tail rotor and airframe. The reliability of the analytical model predictions of the airframe vibration response characteristics is validated by comparison with flight test data. The helicopter model of the vibration control system is constructed by calculating the uncontrolled vibrations that occur in the level flight conditions and the vibrations generated by the HHC actuation, and then performing off-line system identification. Using the constructed system model, the optimal control to reduce the main rotor vibratory hub load is evaluated. Then the optimal control for airframe vibration reduction is investigated, and the control inputs and vibration characteristics of the optimal main rotor vibratory hub load reduction control and the optimal airframe vibration reduction control are compared and discussed. It is observed that at low-speed flight condition, a larger control input is required to reduce airframe vibration than to reduce the vibratory hub load and that the optimum control input for airframe vibration reduction does not reduce the ? component of the vibratory hub load.